Ultrasound Estimated Bladder Weight in Asymptomatic Adult Females - Al-Shaikh, Ghadeer; Al-Mandeel, Hazem (Urology Journal, 2012)
PURPOSE: To estimate the bladder weight by automated ultrasound method (BladderScan BVM 9500) in adult females without lower urinary tract symptoms and to assess both the intra-observer and interobserver reproducibility of this method. MATERIALS AND METHODS: Healthy volunteers were recruited in King Khalid University Hospital from hospital staff and patients attending the gynecological clinic over a period of six months. All women were screened for any lower urinary tract symptoms using a validated short version of Urinary Distress Inventory questionnaire. BladderScan BVM 9500 device (Diagnostic Ultrasound, Bothell, WA) was used to measure bladder wall thickness, bladder volume, and calculated bladder weight. RESULTS: Eighty-five women were included in the study. The mean age was 37.5 years (± 11.1). Mean bladder wall thickness (BWT) was 1.68 mm (95% confidence interval: 1.61 to 1.75) and the mean ultrasound-estimated bladder weight (UEBW) was 32.25 g (95% confidence interval: 31.7 to 32.8). The UEBW intra-observer (ICC: 0.81) and interobserver (ICC: 0.8) reproducibility were excellent while intra-observer (ICC: 0.55) and interobserver (ICC: 0.6) reproducibility for BWT were moderate. No correlation was found between UEBW and age, height, body weight, or bladder volume. CONCLUSION: The estimated bladder weight by automated ultrasound device in asymptomatic adult females yields reproducible measurements and can be used as a reference for future understanding of the changes in bladder weight related to different types of urinary incontinence or voiding disorders.